A Quantitative Model for the Integrated Policy Framework - Adrian, Tobias; Erceg, Christopher; Linde, Jesper; Zabczyk, Pawel (Washington, D.C. : International Monetary Fund, 2020)
Many central banks have relied on a range of policy tools, including foreign exchange intervention (FXI) and capital flow management tools (CFMs), to mitigate the effects of volatile capital flows on their economies. We develop an empirically-oriented New Keynesian model to evaluate and quantify how using multiple policy tools can potentially improve monetary policy tradeoffs. Our model embeds nonlinear balance sheet channels and includes a range of empirically-relevant frictions. We show that FXI and CFMs may improve policy tradeoffs under certain conditions, especially for economies with less well-anchored inflation expectations, substantial foreign currency mismatch, and that are more vulnerable to shocks likely to induce capital outflows and exchange rate pressures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet